Hepatocyte-Specific Expression of Human Lysosome Acid Lipase Corrects Liver Inflammation and Tumor Metastasis in lal(−/−) Mice - Du, Hong (Am J Pathol, 2015)
The liver is a major organ for lipid synthesis and metabolism. Deficiency of lysosomal acid lipase (LAL; official name Lipa, encoded by Lipa) in mice (lal(−/−)) results in enlarged liver size due to neutral lipid storage in hepatocytes and Kupffer cells. To test the functional role of LAL in hepatocyte, hepatocyte-specific expression of human LAL (hLAL) in lal(−/−) mice was established by cross-breeding of liver-activated promoter (LAP)–driven tTA transgene and (tetO)(7)-CMV-hLAL transgene with lal(−/−) knockout (KO) (LAP-Tg/KO) triple mice. Hepatocyte-specific expression of hLAL in LAP-Tg/KO triple mice reduced the liver size to the normal level by decreasing lipid storage in both hepatocytes and Kupffer cells. hLAL expression reduced tumor-promoting myeloid-derived suppressive cells in the liver of lal(−/−) mice. As a result, B16 melanoma metastasis to the liver was almost completely blocked. Expression and secretion of multiple tumor-promoting cytokines or chemokines in the liver were also significantly reduced. Because hLAL is a secretory protein, lal(−/−) phenotypes in other compartments (eg, blood, spleen, and lung) also ameliorated, including systemic reduction of myeloid-derived suppressive cells, an increase in CD4(+) and CD8(+) T and B lymphocytes, and reduced B16 melanoma metastasis in the lung. These results support a concept that LAL in hepatocytes is a critical metabolic enzyme in controlling neutral lipid metabolism, liver homeostasis, immune response, and tumor metastasis.